Integrated Crop Management to Control Anthracnose (Colletotrichum gloeosporioides) of Mango - Chowdhury, MNA; Rahim, MA (Journal of Agriculture & Rural Development, 2010)
An experiment was conducted to develop an Integrated Crop Management (ICM) practice for controlling anthracnose (Colletotrichum gloeosporioides) of mango with emphasis on non-chemical means and achieving higher yield. The treatments were T1 = Pruning (P) + Weeding (W) + Spading (S) + Fertilizer application + Garlic Extract (3 times) + Irrigation (14 days interval); T2 = P+W+S + Fertilizer application +GE (2 times) + Dithane M-45 (one time) + Irrigation (14 days interval); T3 = P+W+S + Fertilizer application + Bagging (60 days before harvest) + Irrigation (14 days interval); T4 = P+W+S + Fertilizer application + Dithane M-45 (3 times) + Irrigation (14 days interval) and T5 = Control (Untreated). It was found that T4 treated plant resulted the highest (14%) fruit retention per plant followed by T1 (13.75%). The lowest (8.50%) was obtained from T5 (control) at 60 DAFS. Treatments T4 and T1 produced the highest percentage (94 and 92, respectively) of healthy fruits and the lowest (86%) was obtained from T5 (control). The highest yield was obtained from T4 and T1 treatment (18.88 and 17.47 t/ha, respectively) and the lowest (4.48 t/ha) was found in T5. The highest (26.50) soluble solid was obtained form treatment T4 followed by T1 (25.75) and the lowest (24.00) was recorded from T5. The highest disease incidence and severity was found in T5 (66.67% and 3.00%, respectively). Key words: Mango; integrated management; anthracnose; yield. DOI: 10.3329/jard.v7i1.4430 J Agric Rural Dev 7(1&2), 115-120, June 2009